Globalización, corrupción y responsabilidad social (2014)
This paper aims to inform about the problem of corruption, its importance and the need for public and corporate policies in order to eradicate and fight it in all economic and social sectors, as well as in private and government organizations. Primary and secondary sources were used to know the extent of corruption, its presence in developed and developing countries and the need of employing ethical and moral values to try to educate people and to increase awareness about the duty they and their institutions have, to deal with this crime, establishing social responsibility programs under the observance of ethical principles. Some international organizations and business associations, with their practices in favor of honesty and transparency, have achieved positive results